Young people's views about the purpose and composition of research ethics committees: findings from the PEARL qualitative study. Issue 1 (December 2016) - Audrey, Suzanne; Brown, Lindsey; Campbell, Rona; Boyd, Andy; Macleod, John
Abstract Background Avon Longitudinal Study of Parents and Children (ALSPAC) is a birth cohort study within which the Project to Enhance ALSPAC through Record Linkage (PEARL) was established to enrich the ALSPAC resource through linkage between ALSPAC participants and routine sources of health and social data. PEARL incorporated qualitative research to seek the views of young people about data linkage, including their opinions about appropriate safeguards and research governance. In this paper we focus on views expressed about the purpose and composition of research ethics committees. Methods Digitally recorded interviews were conducted with 48 participants aged 17–19 years. Participants were asked about whether medical research should be monitored and controlled, their knowledge of research ethics committees, who should sit on these committees and what their role should be. Interview recordings were fully transcribed and anonymised. Thematic analysis was undertaken, assisted by the Framework approach to data management. Results The majority of interviewees had little or no specific knowledge of ethics committees. Once given basic information about research ethics committees, only three respondents suggested there was no need for such bodies to scrutinise research. The key tasks of ethics committees were identified as monitoring the research process and protecting research participants. The difficulty of balancing the potential to inhibit research against the need to protect research participants was acknowledged. The importance of relevant research and professional expertise was identified but it was also considered important to represent wider public opinion, and to counter the bias potentially associated with self-selection possibly through a selection process similar to 'jury duty'. Conclusions There is a need for more education and public awareness about the role and composition of research ethics committees. Despite an initial lack of knowledge, interviewees were able to contribute their ideas and balance the rights of individuals with the wider benefits from research. The suggestion that public opinion should be represented through random selection similar to jury duty may be worth pursuing in the light of the need to ensure diversity of opinion and establish trust amongst the general public about the use of 'big data' for the wider public good.